Qualitative study of ablation process on PMMA by using interferometer technique - 446019 Hanani Yahaya @ Jaafar; Mohamad Khairi Saidin; Noriah Bidin, 1957-; Malaysian Science and Technology Congress (2004 : Sri Kembangan, Selangor) (Skudai : Universiti Teknologi Malaysia, 2004)
40